Authorship in the coverage of the war in Ukraine: Newsroom work takes precedence over correspondents’ dispatches - Campo, Elena (2024)
The war in Ukraine has grabbed headlines around the world. This analysis asks who is covering it and what this says about war reporting. The advent of the Web and the subsequent polarization of the media pits the constant demand for information against the journalistic expectation of calm analysis. While traditional media seem to guarantee credibility, more and more people are turning to alternative information providers. To explore these changes’ repercussions on war correspondents, this study analyzes 11,268 bylines of the news on Ukraine published digitally by the most widely read newspapers in Spain (El País, El Mundo, El Correo, and La Vanguardia) and the USA (The Wall Street Journal, The New York Times, USA Today and New York Post), during the first week of the conflict, from February 24 to March 2, 2022. Through these, the authors’ working relationship with each newspaper is investigated, employing LinkedIn or Twitter when necessary. While relevant literature suggests that freelancers and agencies dominate international news, this analysis concludes that most of the war coverage (65,64%) has been generated in newsrooms, away from the frontline. While confirming the significant contribution of agencies and a decreasing presence of freelancers, it also confirms the survival of foreign bureaus.